EFFICACY OF SOFT TISSUE MOBILIZATION WITH MEDIAL TAPING ON KNEE PAIN AND FUNCTION ON EXCESSIVE LATERAL PRESSURE SYNDROME (ELPS) IN COLLEGE STUDENTS - Vinosh, Kumar (2018)
Anterior Knee pain (AKP) is one of the common complaints among active individuals. AKP often results with tightness in the lateral patellar retinaculum which tends to rise of pressure in the lateral surface of patella which is termed as excessive lateral pressure syndrome (ELPS). The common management for the AKP is not effective in ELPS. Therefore, a separate form of management should be incorporated in ELPS. The aim of the study is to identify the efficacy of the Soft tissue mobilization with medial taping on pain and function in ELPS in college students. 58 students who are studying in selected colleges, with diagnosis of specifically ELPS were involved in the study using random sampling method. All the students were divided into equal groups. Group A with Soft tissue mobilization and medial taping was given and Group B with medial taping only. Study was conducted for 6 weeks. Pain was assessed by Numerical pain rating scale (NPR) and functional disability was assessed using Kujala patellofemoral scoring. Data were collected before and after the study were analysed using SPSS. The result of the study shows that there was a significant difference shown in both the groups. Study concludes that application of Medial Taping with the Soft tissue mobilization produce a better result in pain reduction and improvement of the function when compared to the Medial Taping only